2021
DOI: 10.3390/diagnostics11050802
|View full text |Cite
|
Sign up to set email alerts
|

Retinal and Optic Disc Vascular Changes in Patients Using Long-Term Tadalafil: A Prospective Non-Randomized Matched-Pair Study

Abstract: Retinal, choroidal and optic disc vascularity has never been evaluated in patients taking PDE5is long-term. The aim of our study was to evaluate the neurostructural and vascular changes after long-term use of tadalafil, using spectral domain (SD)-optical coherence tomography (OCT) and optical coherence tomography angiography (OCTA). In the present clinical trial, 27 patients who have been taking tadalafil 20 mg on alternate days (OAD) for at least 6 months (Group A) were enrolled. The matched group consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Nevertheless, the effect of sildenafil on the retinal vascular structure is not limited to the mentioned hypotheses. Capece et al showed a decreased vessel density of retina and optic nerve in the group of participants consuming tadalafil for more than 6 months compared with the matched control group, and they theorize that this medication could damage retinal capillaries [ 25 ]. The vascular effect of 5-PDE inhibitors is not limited to the retina and optic disc; there are several reports of cerebral vascular accident, myocardial infarction, and deep vein thrombosis following consumption of these medications [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the effect of sildenafil on the retinal vascular structure is not limited to the mentioned hypotheses. Capece et al showed a decreased vessel density of retina and optic nerve in the group of participants consuming tadalafil for more than 6 months compared with the matched control group, and they theorize that this medication could damage retinal capillaries [ 25 ]. The vascular effect of 5-PDE inhibitors is not limited to the retina and optic disc; there are several reports of cerebral vascular accident, myocardial infarction, and deep vein thrombosis following consumption of these medications [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the percentage of patients who discontinued the treatment is still high. In particular, PDE5-is are associated with several adverse effects, reducing the patients' compliance and drop-out [7]. On the other hand, several nutraceutical compounds, supplemented as single agents and/or in different combinations, have been reported to offer benefits in the treatment of ED, without adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…While phosphodiesterase type 5 inhibitors (PDE5is) can effectively treat ED, they do not provide long-term improvement in vascular dysfunction. 11 The concept of the visceral adiposity index (VAI) was introduced as an indicator of adipose tissue dysfunction, combining HDL cholesterol, triglyceride levels, body mass index (BMI), and waist circumference (WC) into a gender-speci c formula. 12 Our recent studies have shown that each unit increase in VAI is associated with a 1.3-fold increased risk of ED in men.…”
Section: Introductionmentioning
confidence: 99%